Towards multilingual education: Basque educational research from an international perspective - Zou, Huimin (Language in society, 2011)
Multilingual education in the Basque Autonomous Community (BAC) exemplifies the implementation of such policies, which have exerted tremendous impact on students' language proficiency, academic achievement, identities, and language attitudes. Chs. 3 and 4 focus on the use of Basque as the medium of instruction and discuss its influence on students' linguistic and academic abilities. Since the late 1970s and early 1980s, there have been an increasing number of Basque schools that teach subjects in the minority language., The local government, school authorities, and teachers have made great efforts to promote the use of Basque. The teaching of English in Basque has several prominent characteristics that are worth mentioning, such as the early introduction of English in school and the teaching of English through the Content and Language Integrated Learning method.